Extension of holomorphic mappings for few moving hypersurfaces - Si, Duc Quang (Ukrains’kyi Matematychnyi Zhurnal, 2012)
We prove the big Picard theorem for holomorphic curves from a punctured disc into $P^n(C)$ with $n + 2$ hypersurfaces.We also prove a theorem on the extension of holomorphic mappings in several complex variables into a submanifold of$P^n(C)$ with several moving hypersurfaces.